Surface Wettability of Oxygen Plasma Treated Porous Silicon. (16th January 2014) - Jiang, Lei; Li, Songyan; Wang, Jiqian; Yang, Limin; Sun, Qian; Li, Zhaomin
Abstract : Oxygen plasma treatment on porous silicon (p-Si) surfaces was studied as a practical and effective means to modify wetting properties of as-fabricated p-Si surfaces, that is, contact angles of the p-Si materials. P-Si samples spanning a wide range of surface nanostructures have been fabricated which were subjected to a series of oxygen plasma treatments. Reduction of the p-Si surface contact angles has been systematically observed, and the surface activation rate constant as a function of different pore geometries has been analyzed to achieve an empirical equation. The underlying diffusion mechanisms have been discussed by taking into account of different pore diameters of p-Si samples. It is envisaged that such an approach as well as the corresponding empirical equation may be used to provide relevant process guidance in order to achieve precise control of p-Si contact angles, which is essential for many p-Si applications especially in biosensor areas.